PENJAMINAN MUTU INTERNAL PENDIDIKAN MELALUI TOTAL QUALITY MANAGEMENT (TQM) BERBASIS KOMPETENSI KERJA - Indah Inayatur Rohmah (Hijri, 2025)
AbstractThis research aims to explore internal quality assurance of education through work competency-based Total Quality Management (TQM). The background to this research is driven by the need to improve the quality of education so that graduates can meet the demands of an increasingly competitive industry and labor market. This research uses qualitative data collection through in-depth interviews and observations at SMK Darussalam Banyuwangi. Data sources in this research include primary and secondary data. Primary data was obtained through in-depth interviews with school principals, teachers, education staff and students, as well as direct observation of the process of implementing Total Quality Management (TQM) in educational institutions. Secondary data includes official documents such as work competency-based curricula, education quality reports, and government policies regarding the implementation of TQM. The data analysis technique used is a qualitative approach with the Miles and Huberman interactive model. To ensure the validity of the data, this research uses triangulation techniques. Triangulation is carried out through comparison of data from various sources, such as interviews, observations and documentation. This research identified three main findings: first, work competency as a basis for quality assurance, which shows the importance of a competency-based curriculum in preparing students for the world of work; second, an integrated managerial system that integrates all aspects of educational management to ensure an effective learning process; and third, collaboration and stakeholder participation involving all related parties in quality improvement efforts. The research results show that the application of work competency-based TQM not only improves the quality of education but also the relevance of graduates to industry needs..